The Stony Path of Management Geography - Lech Suwala; Rolf D. Schlunze (SIEM Bulletin, 2019)
Given their central role in economic decisionmaking at the firm-level, one might be inclined to assume that the role of Managers and of Management, would occupy a central place in the field of Economic Geography. In existing literature from the field, however, the `Manager' remains a `lonesome or, more precisely, a fragmented maverick'.
Keywords: M11; M16; A12; R00; B59; 330; Management; Economic Geography; Management Geography; Geography of the Firm; International Business